Phosphate glasses containing monodisperse Fe3−δO4@SiO2 stellate nanoparticles obtained by melt-quenching process - Orives, Juliane Resges [UNESP]; Pichon, Benoit P.; Mertz, Damien; Sartori, Kevin; Begin-Colin, Sylvie; Viali, Wesley Renato [UNESP]; Lima Ribeiro, Sidney J. [UNESP]; Nalin, Marcelo [UNESP] (Elsevier, 2020)
The challenge to obtain stable glasses containing monodisperse magnetic nanoparticles with controlled size and shape is an exciting and almost unexplored field of research. Such new materials can be used in magneto-photonics or ultra-sensitive magnetic sensors. In this work, for the first time, colorless and transparent bulk glasses containing monodisperse 20 nm Fe3−δO4 nanoparticles were prepared by a melt-quenching route. Magnetic nanoparticles were synthesized by thermal decomposition and covered with a stellate mesoporous silica shell in order to protect them against dissolution during the glass melting process. The incorporation of nanoparticles into glasses and the ideal parameters obtained for this system are discussed. The new nanocomposite materials were characterized in order to investigate the structure, thermal, and magnetic properties. Such an original approach is a very promising way to incorporate a wide panel of nanoparticles, including metallic, bimetallic and metal oxide nanoparticles, into a variety of glasses providing new properties to these materials.
Keywords: Coacervate; Glass; Iron oxide nanoparticles; Magnetic materials